2016
DOI: 10.1209/0295-5075/114/10003
|View full text |Cite
|
Sign up to set email alerts
|

Stability of columnar order in assemblies of hard rectangles or squares

Abstract: Lattice theory and statistics PACS 64.60.De -Statistical mechanics of model systems PACS 64.60.Bd -General theory of phase transitionsAbstract -A system of 2 × d hard rectangles on square lattice is known to show four different phases for d ≥ 14. As the covered area fraction ρ is increased from 0 to 1, the system goes from low-density disordered phase, to orientationally-ordered nematic phase, to a columnar phase with orientational order and also broken translational invariance, to a high density phase in whic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 67 publications
2
31
0
Order By: Relevance
“…For the latter case, it was erroneously assumed in Ref. [6] that the contributions from left and right interfaces are identical.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the latter case, it was erroneously assumed in Ref. [6] that the contributions from left and right interfaces are identical.…”
Section: Discussionmentioning
confidence: 99%
“…In our calculations we assumed that the ordered phases have perfect order, thereby ignoring the presence of defects in the bulk phases. Defects may be included in a systematic manner, as was done for the case of 2 × d rectangles [6]. However, it was found that the corrections appearing from including overhangs were more dominant than that arising from including defects when d was small as is the case for hard squares.…”
Section: Discussionmentioning
confidence: 99%
“…We note that in this phase, two sublattices are preferentially occupied, one with A- type particles and the other with B-type particles. The stabilization of the columnar phase by creating vacancies is an example of order by disorder, prototypical example being the hard square gas [13][14][15][16][17][18].…”
Section: Two Types Of Particles (Zmentioning
confidence: 99%
“…For other shapes, Monte Carlo are more reliable than predictions based on approximate theories. Examples include rods [43][44][45], pentamers [46], tetronimos [47], squares [48][49][50][51][52][53], etc. In three dimensions, the results are much fewer and the detailed phase diagram is known only for long rods [54,55].…”
Section: Introductionmentioning
confidence: 99%